2009
DOI: 10.1111/j.1440-169x.2009.01110.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial expression patterns for the tumor suppressor Maspin and its binding partner interferon regulatory factor 6 during breast development

Abstract: Interferon regulatory factor 6 (IRF6) is a non-canonical member of the interferon regulatory factor family of transcription factors. We recently identified IRF6 as a novel Maspin-interacting protein in mammary epithelial cells. Maspin is a tumor suppressor in the breast and has also been implicated in mammary gland morphogenesis. To explore a possible role for IRF6 in conjunction with Maspin during mammary gland growth and differentiation, we examined the expression of IRF6 and Maspin during post-utero mammary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…IRF6 has recently been shown to promote differentiation of zebrafish periderm by directly regulating the expression of Grainyhead-like 3 (GRHL3) (37). Despite these observations, subcellular localization studies indicate that IRF6 localizes to the cytoplasm both in vivo and in vitro (9,21,38,39) suggesting that, as with other IRF family members, IRF6 exists in an autoinhibited state until activated by phosphorylation (40). Although previous studies have indicated that IRF6 is subject to phosphorylation, the kinase responsible has not been identified.…”
Section: Discussionmentioning
confidence: 64%
“…IRF6 has recently been shown to promote differentiation of zebrafish periderm by directly regulating the expression of Grainyhead-like 3 (GRHL3) (37). Despite these observations, subcellular localization studies indicate that IRF6 localizes to the cytoplasm both in vivo and in vitro (9,21,38,39) suggesting that, as with other IRF family members, IRF6 exists in an autoinhibited state until activated by phosphorylation (40). Although previous studies have indicated that IRF6 is subject to phosphorylation, the kinase responsible has not been identified.…”
Section: Discussionmentioning
confidence: 64%
“…The role of Irf6 during development is largely unknown, however its role during epidermal and mammary formation highlights its effect on the cell cycle and cellular differentiation [2], [3], [26]. The decrease in proliferation throughout the Irf6 −/− lingual tissue suggested that (1) Irf6 was acting directly on the SPM in a cell-autonomous fashion to affect cell cycle progression and/or (2) acting in a non-cell-autonomous fashion on the CNC, which then may signal back to the SPM, similar to the results seen in the Wnt1-cre;Tgfbr2 F/F mice.…”
Section: Discussionmentioning
confidence: 99%
“…mammary gland, in pregnant mice (35, 36). Earlier, we showed that maspin is expressed in prostate epithelial cells, Pten +/+ , but not in Pten −/− (16).…”
Section: Resultsmentioning
confidence: 99%